Formulation and Physical Stability Test of Essence Sheet Mask Preparation from Kokang Leaf Extract (Lapisanthes amoena) - Tsaniya Ukhti Nabilah; Ika Ayu Mentari (Program Studi Farmasi Universitas Mandala Waluya, 2023)
Kokang leaf ethanol extract contains secondary metabolite compounds such as phenolics, flavonoids, tannins, steroids, and saponins that have antioxidant and antibacterial effects and play a role in wound healing. Seeing the potential in kokang leaves (Lepisanthes Amoena) until now the use of kokang leaves is still very lacking, therefore the need for innovation in the use of leaves, one of which is by developing a formulation of essence sheet mask preparations from kokang leaf extract (Lepisanthes Amoena). Formulations in the form of essence sheet masks are currently the latest developments in cosmetic preparations. The purpose of this study was to formulate and test the physical stability of the essence sheet mask preparation from the extract of kokang leaves. The preparation is made as many as 3 formulas, the leaf extract used is 0.1% (F1), 0.3% (F2), and 0.5% (F3). The evaluation carried out includes organoleptic tests (color, aroma, and texture), homogeneity tests, pH tests, room temperature stability tests, viscosity tests, and hedonic tests (favorability and irritation). The results showed that the preparation of the essence sheet mask was a thick solution with a characteristic green and homogeneous odor. The preparation of the essence sheet mask is stable at room temperature without any change. The pH value of the preparation essence sheet mask 5 – 6. Viscosity with a viscosity of 2,217 cP. A hedonic test of 12 panelists showed that the average favorability of all categories was superior to F2 (0.3%) and there was no irritation to the entire formula.